Performance Analysis of Position Tracking Control With PID Controller Using An Improved Optimization Technique - Chai, Mau Shern; Chong, Shin Horng; Jaafar, Hazriq Izzuan; Chong, Chee Soon; Ghazali, Rozaimi; Md Sam, Yahaya (International Journal of Mechanical Engineering and Robotics Research, 2019)
An Electro-Hydraulic Actuator (EHA) system is usually utilized in production industry such as automotive industry which requires precision, high force and long operating hours. When dealing with the production of engineering parts that require precision, high force and long operating hours, a controller is usually required. It is observed from the literature, an appropriate tuning technique is essential in order to obtain optimal controller’s performance. Therefore, a computational tuning technique, namely Priority-based Fitness Particle Swarm Optimization (PFPSO) is proposed to obtain the parameters of the Proportional-Integral-Derivative (PID) controller in this paper. The performance of the EHA system will be evaluated and compared based on the priority characters of the PFPSO tuning technique, which included settling time and overshoot percentage that affect the output results of the EHA system. As a result, it is observed that the priority based on settling time produced a better result, which enhances the steady-state performance of the EHA system that fulfills the requirement of the precision control